A New Deal for China's workers? - Estlund, Cynthia (Harvard University Press, 2017)
This book takes a comparative look at China's labor pains and the reforms taking shape in their wake. Some recent developments in China - rising strike levels, a surge of union organizing, and a raft of reforms - seem to echo the American New Deal experience. But even as China's leaders hope to replicate the prosperity and stability that flowed from the New Deal labor reforms, they are irrevocably opposed to the independent trade unions that were the central actors in both spurring and carrying out those reforms. In China the specter of an independent labor movement both drives and constrains every facet of China's labor policy, both its reforms and its use of repression. If China's workers get their New Deal, it will be a New Deal with "Chinese characteristics," very unlike what workers in the West achieved in the mid-20th century.--